Pengembangan E-Modul IPA Berbasis 5D Thinking Terintegrasi Islam Dalam Menyongsong SDGS 2025 - Syarif, Muhammad Ilham; Tania , Anita; Permana, Niki Dian; Sulaimon, Jamiu Temitope (Indonesian Journal of Education and Learning, 2025)
This research was motivated by the scarcity of teaching materials in the form of e-modules based on 5D Thinking at MTsN 1 Pekanbaru City. Science learning often relies on textbooks as learning material, while the use of modules or electronic modules (E-Modules) is still limited. The use of teaching materials has an important role in the smooth process of teaching and learning science in the classroom. Utilizing this teaching material has many advantages, including encouraging students to improve their independent learning skills with the help of learning videos and photos that can be accessed via barcode. This research aims to produce science/MTs e-module teaching materials based on 5D Thinking on the structure of the earth and its development. The research was carried out by the author using the research and development method with the Plomp development model. This research step consists of 3 stages, namely the initial investigation phase (preliminary research), the prototype formation phase (prototyping stage), and the assessment phase (assessment phase). The data in this research is in the form of qualitative descriptive and quantitative descriptive data using validity questionnaires in the form of material validators, teaching material validators, Islamic values ​​validators, science teacher practicality questionnaires, and responses from 29 students from class VIII. The validity results of the product developed were declared very valid based on validation results by learning materials experts with a score of 96%, teaching materials experts with a score of 97%, Islamic values ​​integration experts with a score of 97%, with an overall average validity score of 96.6%. It was declared very practical by the teacher with a score of 96.25%, and declared very good by students with a score of 84.6%. Based on the assessment of limited test experts, the SMP/MTs science e-module based on 5D Thinking on earth structure material and its developments is suitable for use in science learning.